Women in Board of Directors and Real Earnings Management: Accretive Share Buyback in Malaysia - Alquhaif, Abdulsalam Saad; Abdul Latif, Rohaida; Chandren, Sitraselvi (Macrothink Institute, 2017)
Gender diversity of boards and reporting of earnings are two most debated issues in the corporate world.In this context, the paper explores how the presence of women directors on the corporate board influence real earnings management through accretive buyback programs. Using a sample of 601 firms’ observations that engage in accretive share buyback from 2010-2015, the findings reveal that existence of women directors on the board is associated with less engagement in accretive share buyback activities. We further find that firms with a higher number of independent directors are less likely to practice real earnings management through accretive buyback programs.Our paper contributes to the debate on gender diversity on boards and its influence on the utilisation of accretive buyback programs as a tool to real earnings management.